Septum pyramidal adjustment and repositioning - a conservative and effective rhinoplasty technique - Atolini Junior,Nedio (2019)
Abstract Introduction: In rhinoplasty, the nasal dorsum has important relevance regarding the esthetic and functional aspects of the surgery. Its reduction should be performed with maximum accuracy and controlled resection to prevent or minimize potential complications. The septum pyramidal adjustment and repositioning consists of a conservative surgical technique of the nasal dorsum, which does not require the detachment of the upper lateral cartilages of the nasal septum, allowing the remodeling of the nasal dorsum while maintaining esthetic lines and nasal function, potentially reducing frequent complications in more traditional surgeries. Objective: To describe the septum pyramidal adjustment technique in detail, presenting its advantages and disadvantages in relation to the other surgical approaches, as well as to disclose results of this surgical procedure in patients submitted to primary rhinoplasty in a specific hospital. Methods: The medical records of all patients submitted to surgery from 2011 to 2015 through this surgical technique were evaluated by the same team. Of these cases, certain variables were analyzed such as gender, age, indication for reoperation and surgical complications. Results: 153 patients underwent rhinoplasty through septum pyramidal adjustment. Of these, 13 patients experienced an indication for a second surgery and four had some type of postoperative complication. Conclusion: The septum pyramidal adjustment surgical technique is a simple procedure, as it does not require the reconstruction of the nasal dorsum. It has a low number of complications and preserves the anatomical structures.